Who can be nudged? Examining nudging effectiveness in the context of need for cognition and need for uniqueness - Moritz Ingendahl; Dennis Hummel; Alexander Maedche; Tobias Vogel (Journal of Consumer Behaviour, 2021)
In the last decade, there has been a growing research focus on the subtle modifications of choice architecture that have strong effects on consumer behavior and are subsumed under the term nudging. There is still little research, however, on how different nudges influence individuals with different personality characteristics. An experimental online shopping scenario is used to test whether a customer's Need for Cognition and Need for Uniqueness moderate the effectiveness of two of the most prominent nudges—defaults and social influence. Two experiments with samples stratified by age, gender, and education (total N = 1,561) reveal that defaults and social influence have the predicted impact on a customer's decision. Across both studies, nudge effectiveness was partially impacted by Need for Cognition and not impacted at all by Need for Uniqueness. These findings imply that both types of nudges are strong and robust techniques to influence consumer decision-making and are effective across different levels of consumer's Need for Cognition or Need for Uniqueness.
Keywords: 320